Formation of Coconut Oil By–Product Protein Concentrate–Pectin Through Electrostatic Interaction to Improve Emulsifying Properties - Kurniawati, Ajeng Dyah; Hidayat, Chusnul; Setiowati, Arima Diah (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2023)
Coconut oil has been rising in popularity because of its health benefits. Coconut oil by-product or blondo is obtained during wet processing for virgin coconut oil production. It has a high protein content and can be utilized as an emulsifier in food products. This research aimed to examine the effect of pH, protein and pectin concentration on the stability and emulsification properties of heat-treated blondo protein concentrate-pectin complexes. The best conditions of pH, pectin and protein concentration for forming blondo protein concentrate-pectin complexes through electrostatic interaction were obtained by mixing blondo protein concentrate solution (0.5 to 1.5 wt%) with pectin (0.1 to 0.35 wt%) at different pH conditions (3 to 5). These particles were tested for emulsifying activity, stability and heat stability (85±2 °C; 15 minutes). Complexes formed using 0.5 wt% protein and 0.35 wt% pectin at pH 4 obtained from these experiments had the best zeta potential value and particle size, respectively -25.88 mV and 192.92 nm. Complexation between protein and pectin enhanced the emulsion activity index (EAI), emulsion stability index (ESI) and protection of self-aggregation protein during heating. Complexes that were formed remain stable across a range of pH values (pH 4 to 7). Thus, blondo protein concentrate-pectin complexes formed in this research through electrostatic interaction have better functional properties than the blondo protein concentrate before complexation. Emulsions created using blondo protein concentrate-pectin complexes through electrostatic interaction also had a higher value of emulsifying activity, stability and heat stability than emulsions with blondo protein concentrate alone.